A rare ophthalmic condition associated with primary hyperparathyroidism (PHPT): sclerochoroidal calcification (SC). (3rd August 2019) - Abouzaid, Mona; Al-Sharefi, Ahmed; Artham, Satish; Masri, Ibrahim; Kotagiri, Ajay; Joshi, Ashwin
Summary: An 82-year-old male with a proven diagnosis of primary hyperparathyroidism (PHPT) was found to have bilateral changes in the fundi during a routine eye examination which were consistent with SC. In this report, we discuss the link between SC and PHPT and question the need for prospective observational studies to establish the true association between these conditions. Though screening PHPT patients for SC might not be justified/warranted given the benign course of the latter, patients with SC need to be assessed for PHPT, as the former may be the first clue to an underlying treatable systemic disease. Learning points: Sclerochoroidal calcifications (SCs), though rare and harmless, could be associated with an underlying systemic disease, such as primary hyperparathyroidism (PHPT). Biochemical screening for hypercalcaemia is a simple, cheap and widely available tool that could facilitate an identification of undiagnosed PHPT in patients with SC. A joint care by endocrinologists and ophthalmologists is warranted for those patients, as thorough investigations and long-term follow-up plans are crucial.